Essential public health functions of public health personnel in subdistrict health-promoting hospitals, Thailand - Wonpen Yodkong; Pramote Wongsawat (Wolters Kluwer Medknow Publications, 2023)
Background: In Thailand, public health service roles have been defined by the Ministry of Public Health, while essential public health functions (EPHFs) were not assigned as necessity health-care service activities responding to the missions of primary care units. Objectives: The aims were to determine the EPHFs and compare the necessity of performance and the actual performance according to the EPHFs of public health personnel in the subdistrict health-promoting hospitals (SHPHs). Materials and Methods: The exploratory sequential design of mixed methods was employed. The first phase consisted of three methods: a focus group discussion, a nominal group technique, and a cross-sectional survey used to determine the EPHFs. The second phase was to compare the necessity of performance and the actual performance according to the EPHFs of the personnel using a cross-sectional survey. The 285 SHPH directors in the second health region as samples were selected by random clusters. Results: The findings revealed that 14 EPHFs and the necessity of performance average were higher than the actual performance average in the 14 EPHFs and 212 indicators with significance at a level of 0.05. The means of health assessment and primary medical care (EPHF3) presented the smallest difference, whereas Thai traditional and alternative medicines (EPHF11) indicated the largest average difference. Conclusions: EPHFs would be applied for setting a framework of working scope as policies and EPHFs could be recommended for use as individual guidelines or organizational assessment manuals to develop organizations efficiently.